The incidence of reading comprehension strategies in the results of the reading skill of the ket test taken by students attending the seventh year of basic education at Cardinal Spellman Girls´ School during the third trimester, 2010-2011 school year - Peñafiel, Lorena (2011)
This test has now been taken for the past 6 years and through the evaluation of the results, it can be observed that the reading and writing scale has the lowest range. So the problem is the lower results of the KET in the Reading and Writing skills. Therefore, new approaches must be taken to address the problem of poor comprehension in Reading and Writing skills as shown in the KET results. Obviously, when a student faces the reality of a low or failing grade and the impossibility of improving their test results, there will be problems; such as possible school dismissal or a total rejection towards learning the English language. Also, we can find problems in the normal reading tests such as reading comprehension problems or reasoning difficulties.Reading is one of the basic skills of language learning, and there are a wide range of strategies available to improve this skill. Some causes for the difficulties in this such as boring or age inappropriate reading materials, lack of sequential programs or the use of failed methodologies can be corrected or at least improved with a well established reading program. The KET test is a standardized ESOL test taken by the University of Cambridge designed around four essential qualities: validity, reliability, impact and practicality. The results are displayed graphically in the scale Exceptional, Good, Borderline and Weak. In addition, candidates receive a standardized score for the entire exam on a fixed scale out of 100.Due to this testing approach, it was impossible to analyze each student's results just in the reading skill. Therefore, this research is based on a mock test taken by the students before the application of any Reading strategy and a post test taken by the students after the process.